Multi-spectral autofluorescence variability of the individual retinal pigmented epithelial cells in healthy aging eyes - Daniel M. W. Lee; Min Zhang; Valerie C. Snyder; Ethan A. Rossi (Scientific Reports)
Abstract The retinal pigment epithelium (RPE) is vital for the healthy function of the retina. Cellular level changes in the RPE are not visualized with current clinical techniques due to a lack of spatial resolution. Fluorescence adaptive optics scanning light ophthalmoscopy (AOSLO) can image RPE cells by utilizing their intrinsic autofluorescence (AF). The RPE AF has been imaged with only a few discrete excitation and emission bands and the multi-spectral AF has not been interrogated systematically at the level of single cells. In this study, we imaged 16 healthy eyes (ages 20-75) with AOSLO to investigate the multi-spectral AF as a function of age and wavelength with excitation from 650 - 805 nm. Quantitative analysis showed that 720 nm light produced images with the highest SNR (65.0 dB). Spatial AF variability showed a trend to increase with aging, suggesting increased heterogeneity in RPE AF with age. Spatial variability in the multi-spectral fluorescence of RPE cells with age may be a consequence of normal age-related loss of RPE cells. Multi-spectral fluorescence AOSLO provides new insight into aging related changes to RPE cells and may be a useful tool for studying diseases that affect the RPE, such as age-related macular degeneration (AMD).